Guide to the communication strategy of native advertising - Wang, Yao; Mohd Zawawi, Julia Wirza; Ahmad, Abdul Muati @ Zamri; Sern, Tham Jen (Human Resource Management Academic Research Society, 2022)
To adapt to the ever-changing digital technology revolution and the challenges posed by the information explosion in the communication environment, traditional advertising has sought reconstruction and enhancement. Native advertising is one of the advertising industry's innovations and breakthroughs, appearing on a variety of platforms such as social media, news websites, and search engines. Native advertising's major goal is to provide consumers with relevant information, unique content, and a positive experience. The ongoing development of native advertising has inspired many scholars to discuss it. However, the native advertising research stream is still in its fancy. Thus, this conceptual paper reviews the various definition of native advertising. Based on the various definition, this paper aims to discuss the communication strategy of native advertising from three different levels that are format, content, and users. The results imply that native advertising’s communication strategy includes embedding, creativity, and interactive communication from format, content, and users respectively. These three communication strategies have made great contributions to the communication and development of native advertising.